A new technique to synthesize silver/polyvinyl alcohol nanocomposite: characterization and nonlinear optical properties / W. Mahmood Mat Yunus … [et al.] - Mat Yunus, W. Mahmood; Yap, Wing Fen; Faraji, Nastaran; Tamchek, Nizam; Talib, Zainal Abidin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
A new technique for preparing silver/polyvinyl alcohol (PVA) nanocomposites is introduced. The silver/PVA nanocomposites are prepared via quick precipitation method, using hydrazine as a reducing agent. The characterization of the sample is investigated by UV Visible spectroscopy (UV-Vis), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The silver nanocomposites are nearly spherical and the size is in the range of 10 to 25 nm. The nonlinear refractive index and nonlinear absorption were measured using a sensitive Z-scan technique. It is shown that the novel synthesized sample has negative nonlinear refractive index in the order of 10-8. The results also proved that the nonlinear refractive index increases as the amount of reducing agent increases. The novel sample has a high application in nonlinear optical devices.